THE EFFECT OF EARNING PER SHARE, ENVIRONMENT, AND SOCIAL DISCLOSURE ON COMPANY PERFORMANCE (CASE STUDY OF PT. BUMI RESOURCE TBK PER 2018-2022) - Sisca Debyola Widuhung; Aris Machmud (Asosiasi Dosen Muda Indonesia, 2024)
Changes in the orientation of achieving company performance as a result of globalization encourage every company to increase its competitiveness to survive in increasingly fierce market competition, profit achievement is no longer the main performance in assessing performance but involves non-financial aspects that impact investor confidence. the purpose of this research is to identify and analyze the effect of Earning Per Share (EPS), Environmental Disclosure (ESG), and Corporate Social Responsibility on Company Performance. The research method uses a quantitative approach using non-financial company data, in this case, PT. Bumi Research Tbk, which is incorporated in Reuter and Thomson in the 2018 -2022 timeframe, while the data analysis technique uses SPSS version 23 to test hypotheses through simple regression. The results of this study indicate that Earning Per Share, Environmental Disclosure, and Corporate Social Responsibility (CSR) simultaneously do not affect company performance. although it does not affect the company's performance, it is one of the indicators that become a concern for investors in investing, besides that environmental and social disclosure is mandatory from regulations related to corporations, from a financial perspective, but can affect other performance such as an increase in stock prices.